2008
DOI: 10.1016/j.bandc.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Motor asymmetry and substantia nigra volume are related to spatial delayed response performance in Parkinson disease

Abstract: Studies suggest motor deficit asymmetry may help predict the pattern of cognitive impairment in individuals with Parkinson disease (PD). We tested this hypothesis using a highly validated and sensitive spatial memory task, spatial delayed response (SDR), and clinical and neuroimaging measures of PD asymmetry. We predicted SDR performance would be more impaired by PDrelated changes in the right side of the brain than in the left. PD (n = 35) and control (n = 28) participants performed the SDR task. PD participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 52 publications
0
32
0
1
Order By: Relevance
“…Three studies disclosed a worse BVRT-performance for LPD patients (Amick et al 2006a;Starkstein et al 1987;Tomer et al 1993), whereas two studies reported no differences between the groups (Mohr et al 1992;Starkstein et al 1987). A recent study also found a worse performance in LPD patients on a spatial delayed response task (Foster et al 2008). Taken together, seven out of thirteen studies investigating visuospatial memory in asymmetric PD reported no differences between the groups, five found a worse performance for the LPD group, and one study showed a disadvantage for the RPD group.…”
Section: ) Memorymentioning
confidence: 87%
See 1 more Smart Citation
“…Three studies disclosed a worse BVRT-performance for LPD patients (Amick et al 2006a;Starkstein et al 1987;Tomer et al 1993), whereas two studies reported no differences between the groups (Mohr et al 1992;Starkstein et al 1987). A recent study also found a worse performance in LPD patients on a spatial delayed response task (Foster et al 2008). Taken together, seven out of thirteen studies investigating visuospatial memory in asymmetric PD reported no differences between the groups, five found a worse performance for the LPD group, and one study showed a disadvantage for the RPD group.…”
Section: ) Memorymentioning
confidence: 87%
“…Among these, there are further differences in the cutoff-values that were applied. In six studies, the difference between the left and the right score was used (Agniel et al 1991;Cubo et al 2010;Ebersbach et al 1996;Huber et al 1992;Nys et al 2010;Riklan et al 1990), six studies used the ratio between the left-and the right-sided scores (3:1 or 2:1) (Harris et al 2003;Lee et al 2001a, b;Spicer et al 1988;Starkstein and Leiguarda 1993;Starkstein et al 1987) and five other studies used a lateralization index of the symptom severity scores on the left side and on right side (difference/sum) (Clair et al 1998;Dominey et al 1995;Finali et al 1995;Foster et al 2008;Holtgraves et al 2010). Two studies only included patients with exclusively unilateral symptoms (Hietanen and Teräväinen 1989;Huber et al 1989Huber et al , 1989, whereas most of the studies tested patients with bilateral asymmetric symptoms.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…The substantia nigra was identified on the 3 T turbo spin-echo sequence (Foster et al, 2007). This region included both the pars compacta and the pars reticulata.…”
Section: Image Analysismentioning
confidence: 99%
“…Consistent with these visual deficits in LOPD, deficits in visuospatial ability/attention (Norton, Jaywant, Gallart‐Palau, & Cronin‐Golomb, 2015; Poletti et al., 2013) and spatial planning (Cheesman et al., 2005) have been found. Interestingly, a deficit in spatial memory was shown to be associated with smaller substantia nigra volume (using MRI) in LOPD (Foster, Black, Antenor‐Dorsey, Perlmutter, & Hershey, 2008; Those with LOPD have shown significant impairment of working memory on the Digit Span Backward (DSB) task, which was associated with significantly greater depression in one study (Foster et al., 2013) and significantly greater anxiety in another study (Foster et al., 2010). Furthermore, those with LOPD show a deficit in mental rotation related to object‐view (Cronin‐Golomb, 2010; Lee, Harris, & Calvert, 1998).…”
Section: Introductionmentioning
confidence: 99%